Social Presence and Visual Communication in Infographic-Based Autism Parenting Videos on YouTube - Dwi Firmansyah; Oktaviana Purnamasari (UPT Publikasi Ilmiah UNISBA, 2026)
Autism parenting communication in Indonesia continues to face uneven public awareness and persistent social stigma, underscoring the need for effective digital health communication. This study examines how social presence is constructed through visual communication in infographic-based YouTube videos on autism parenting. Five episodes of the Berbeda Itu Kuat series produced by Liputan6 SCTV were analyzed using directed qualitative content analysis. The findings indicate that social presence is expressed through affective, interactive, and cohesive cues in narration, language, and visual design, creating a mediated sense of emotional support and relational closeness. Infographic elements such as icons, symbolic colors, concise text, and structured layouts help translate complex information into accessible visual forms. The videos also reflect adaptation to YouTube’s platform characteristics through short duration and conversational tone. By demonstrating how social presence can be operationalized through infographic-based video design, this study extends health communication scholarship beyond audience perception toward representational practice. Because the analysis focuses on representational construction rather than audience reception, the findings do not address how viewers interpret or respond to these communicative strategies.